Efficacy outcome and sex difference in learning of hypermedia programming skills. - Tam, Sing-Fai (Perceptual & Motor Skills)
86 occupational therapy students participated in a 20-hr. training course in hypermedia programming for selecting functions for development of rehabilitation software. Analyses showed that the training program significantly enhanced their self-efficacy in development of software for clinical practice. The students generally showed a positive attitude towards the feasibility and significance of applying hypermedia programming in occupational therapy, but no significant sex difference in programming self-efficacy was found. Reprinted by permission of the publisher, 1998.